A business plan for a startup of an event e-marketplace and planning solution in Malaysia - Khalil, Nadiah (2021)
SumofEvents is a cloud-based mobile application that offers end-to-end social events planning solution, combining E-marketplace platform and event management tools. Nowadays, every single thing is done ‘Online’. However, there is a lack of one-stop-shop for online event e-marketplace and event planning solution, as well as expensive for vendors to do mass advertising and reach customers. Hence, an on-demand social events planning application will assist vendors/event planners to reach customers with more ease and allow customers to search for and incorporate services required within a single platform. The weddings industry in Malaysia is flourishing with 300,000 weddings recorded per year with average transaction value of RM 50,000 – RM 200,000. SumOfEvents present a diversified business which will not only penetrate the weddings industry, but also other small categories of events with the aim of capturing baseline market share of 5% of weddings industry by Year 5 of incorporation.